Effect of Organic and Inorganic Fertilizer Application and Seedbed Preparation on Potato Yield and Soil Properties on Alisols of Chencha - Boke, Shiferaw (International Journal of Natural Sciences Research, 2014)
A field experiment was conducted for two years (2006 and 2007) during the belg seasons on strongly acid clay loam (Haplic Alisols) soils at Chencha research substation, Southern Ethiopia. The objective was to examine the effect of seedbed preparation methods and organic-inorganic fertilizers on potato tuber yield and soil properties. The experiment was arranged in split-plot design with seed bed preparation methods: hoe plough once (M1), hoe plough twice (M2) and hoe plough thrice (M3) as main plots, and fertilization levels, namely, a control without fertilizer, NP, NPK, NP+FYM, NPK+FYM and FYM as sub plots with three replicates. Results indicated that there were significant (P< 0.05) potato tuber yield differences among sub-treatments. The impact of main treatments showed no yield difference. Application of FYM and NPK significantly increased the yield of potato both years. NP application alone did not influence potato yield but significantly increased when combined with FYM. Exclusion of K from either inorganic or combined inorganic-organic fertilizer treatments significantly decreased tuber yield, suggesting K as a major limiting factor on potato production. Combined application of FYM and NPK gave the highest potato yield (41.28 t/ha). The highest net benefit (birr 23982) and maximum marginal rate of return (1060.8) were also achieved with the combined application of FYM and NPK. This result suggests that combined application of FYM and NPK is suitable for better potato production in the Alisols of Chencha.